Deciphering the acute cellular phosphoproteome response to irradiation with X-rays, protons and carbon ions - Winter, Martin; Dokić, Ivana; Debus, Jürgen; Abdollahi, Amir (Molecular & cellular proteomics, 2017)
Radiotherapy is a cornerstone of cancer therapy. The recently established particle therapy with raster-scanning protons and carbon ions landmarks a new era in the field of high-precision cancer medicine. However, molecular mechanisms governing radiation induced intracellular signaling remain elusive. Here, we present the first comprehensive proteomic and phosphoproteomic study applying stable isotope labeling by amino acids in cell culture (SILAC) in combination with high-resolution mass spectrometry to decipher cellular response to irradiation with X-rays, protons and carbon ions. At protein expression level limited alterations were observed 2 h post irradiation of human lung adenocarcinoma cells. In contrast, 181 phosphorylation sites were found to be differentially regulated out of which 151 sites were not hitherto attributed to radiation response as revealed by crosscheck with the PhosphoSitePlus database. Radiation-induced phosphorylation of the p(S/T)Q motif was the prevailing regulation pattern affecting proteins involved in DNA damage response signaling. Because radiation doses were selected to produce same level of cell kill and DNA double-strand breakage for each radiation quality, DNA damage responsive phosphorylation sites were regulated to same extent. However, differential phosphorylation between radiation qualities was observed for 55 phosphorylation sites indicating the existence of distinct signaling circuitries induced by X-ray versus particle (proton/carbon) irradiation beyond the canonical DNA damage response. This unexpected finding was confirmed in targeted spike-in experiments using synthetic isotope labeled phosphopeptides. Herewith, we successfully validated uniform DNA damage response signaling coexisting with altered signaling involved in apoptosis and metabolic processes induced by X-ray and particle based treatments. In summary, the comprehensive insight into the radiation-induced phosphoproteome landscape is instructive for the design of functional studies aiming to decipher cellular signaling processes in response to radiotherapy, space radiation or ionizing radiation per se. Further, our data will have a significant impact on the ongoing debate about patient treatment modalities.